Primary Amyloid Goiter and Review of Imaging Characteristics. (May 2013) - Chung, R; Pilcher, J
Clinically symptomatic amyloid goiter is extremely rare. We report the case of a 76-year-old male patient under the care of the nephrologists with end stage renal failure of unknown aetiology. Concurrent investigation for a dysphagia causing goiter allowed primary diagnosis of amyloid by targeted fine needle aspiration (FNA) under ultrasound guidance. The imaging features are reviewed across multimodalities. This report highlights the usefulness of FNA in establishing diagnosis and the importance of maintaining clinical suspicion in patients with a concomitant history of a chronic inflammatory process.